Cellular and molecular immunology - Abbas, Abul K.; Lichtman, Andrew H.; Pillai, Shiv (Elsevier/Saunders, 2012)
This updated edition continues to provide a straightforward and concise approach to the subject. It focuses on the experimental observations that underlie the science of immunology at the molecular, cellular and whole organism level, and explores the conclusions that can be drawn from those observations